Imaging Recommendations for Diagnosis, Staging, and Management of Hereditary Malignancies - Majithia, Jinita; Mahajan, Abhishek; Vaish, Richa; Prakash, Gagan; Patwardhan, Saket; Sarin, Rajiv (Indian Journal of Medical and Paediatric Oncology, 2023)
Hereditary cancer syndromes, characterized by genetically distinct neoplasms developing in specific organs in more than one family members, predispose an individual to early onset of distinct site-specific tumors. Early age of onset, multiorgan involvement, multiple and bilateral tumors, advanced disease at presentation, and aggressive tumor histology are few characteristic features of hereditary cancer syndromes. A multidisciplinary approach to hereditary cancers has led to a paradigm shift in the field of preventive oncology and precision medicine. Imaging plays a pivotal role in the screening, testing, and follow-up of individuals and their first- and second-degree relatives with hereditary cancers. In fact, a radiologist is often the first to apprise the clinician about the possibility of an underlying hereditary cancer syndrome based on pathognomonic imaging findings. This article focuses on the imaging spectrum of few common hereditary cancer syndromes with specific mention of the imaging features of associated common and uncommon tumors in each syndrome. The screening and surveillance recommendations for each condition with specific management approaches, in contrast to sporadic cases, have also been described.
Keywords: hereditary cancer syndromes; radiogenomics; cancer; surveillance guidelines